Pengaruh Organizational Citizenship Behavior (OCB) Dan Motivasi Kerja Terhadap Kinerja Karyawan - Delia Deswanty Ali; Abd Rahman Pakaya; Andi Yusniar Mendo (Al-Buhuts, 2024)
This study aims to determine the influence of Organozational Citizenship Behavior (OCB) and Work Motivation on Employee Perfomance at Talaga Jaya Public Hhealth Center, Gorontalo Regency, partially or simultaneously. Furthermore, the approach used in this study was a quantitative approach with correlational methods. The data were collected using a questionnaire. The number of samples was 42 people obtained using the saturated sampling process. The data were then analyzed using multiple regression inferential quantitative analysis. The result showed that (1) Organizational Citizenship Behavior (OCB) has a positive and significant influence on employee performance at Talaga Jaya Public Health Center, Gorontalo Regency by 46,20%. (2) Work motivation has a positive influence on employee performance at Talaga Jaya Public Health Center, Gorontalo Regency, by 36,80%. (3) Organizational Citizenship Behavior (OCB) and work motivation simultaneously have a positive influence on employee performance at Talaga Jaya Public Health Center, Gorontalo Regency, by 83,00%. This indicates that the higher the Organizational Citizenship Behavior (OCB) and work motivation, the employee’s performance will increase.